Comparative safety of direct oral anticoagulants and warfarin in venous thromboembolism: multicentre, population based, observational study. (17th October 2017) - Jun, Min; Lix, Lisa M; Durand, Madeleine; Dahl, Matt; Paterson, J Michael; Dormuth, Colin R; Ernst, Pierre; Yao, Shenzhen; Renoux, Christel; Tamim, Hala; Wu, Cynthia; Mahmud, Salaheddin M; et al.
Abstract : Objective To determine the safety of direct oral anticoagulant (DOAC) use compared with warfarin use for the treatment of venous thromboembolism. Design Retrospective matched cohort study conducted between 1 January 2009 and 31 March 2016. Setting Community based, using healthcare data from six jurisdictions in Canada and the United States. Participants 59 525 adults (12 489 DOAC users; 47 036 warfarin users) with a new diagnosis of venous thromboembolism and a prescription for a DOAC or warfarin within 30 days of diagnosis. Main outcome measures Outcomes included hospital admission or emergency department visit for major bleeding and all cause mortality within 90 days after starting treatment. Propensity score matching and shared frailty models were used to estimate adjusted hazard ratios of the outcomes comparing DOACs with warfarin. Analyses were conducted independently at each site, with meta-analytical methods used to estimate pooled hazard ratios across sites. Results Of the 59 525 participants, 1967 (3.3%) had a major bleed and 1029 (1.7%) died over a mean follow-up of 85.2 days. The risk of major bleeding was similar for DOAC compared with warfarin use (pooled hazard ratio 0.92, 95% confidence interval 0.82 to 1.03), with the overall direction of the association favouring DOAC use. No difference was found in the risk of death (pooled hazard ratio 0.99, 0.84 to 1.16) for DOACs compared with warfarin use. There was no evidence of heterogeneity across centres, between patients with and without chronic kidney disease, across age groups, or between male and female patients. Conclusions In this analysis of adults with incident venous thromboembolism, treatment with DOACs, compared with warfarin, was not associated with an increased risk of major bleeding or all cause mortality in the first 90 days of treatment. Trial registration Clinical trials NCT02833987 .